SME Financial Inclusion for Sustained Growth in the Middle East and Central Asia - Ghassibe, Mishel (IMF Working Papers; Working Paper, 2019)
This paper offers empirical evidence that greater financial inclusion of small and medium enterprises (SMEs) can promote higher economic growth and employment, especially in the Middle East and Central Asia regions. First, we show that countries with higher SME financial inclusion exhibit more effective monetary policy transmission and tax collection. Second, we find substantial employment and labor productivity growth gains at the firm level from access to credit, gains that are higher for SMEs. We also obtain evidence of a substantial positive impact on SME employment and labor productivity growth from improved credit bureau coverage and insolvency regimes. Finally, cross-country aggregate evidence confirms the employment and growth gains from SME financial inclusion, which appear larger in the Middle East and Central Asia than in other regions.